Situation of Official Schools in Erbil City 1980 – 1991 (Raparin Journal of Humanities (RJH), 2020)
The subject of the official study conditions in the city of Erbil is of great historical and cultural importance, especially for the city that historians have confirmed in historical sources as one of the oldest cities in the world.The subject of the official study conditions in the city of Erbil for the period between 1980-1991 did not have the importance of being mentioned by researchers, and scientific research has not been conducted on it. Therefore, there is a scientific necessity to carry out such research. The reason for choosing the study period (1980 - 1991) is that because of the outbreak of the Iran-Iraq war in 1980, all aspects of life were affected by this war. Although this war ended in 1988, its effects and repercussions continued to affect the joints of Life in Iraq and the city of Erbil, in addition to the fact that political problems and convulsions grew and developed in that period until Iraq entered Kuwait in 1990, which resulted in wars and regional and internal problems in Iraq. Since that date, a new historical era has begun in the region.This study consists of an introduction to the topic in addition to two main axes and concluded with a list of sources and appendices, in the entry a summary of the official study in the city of Erbil for the period between 1970 - 1980 was presented, and the first axis was devoted to the political situation and the educational process for the period between 1980 - 1991, and in the second axis The laws, regulations, and educational curricula for the period between 1980 - 1991 are covered.